SIMBOLISME ORNAMEN KUMUDAWATI PADA SINGUP PENDHAPA AGENG MANGKUNEGARAN KARYA MANGKUNEGARA VII - Wisnu Adisukma (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
The contents of this thesis concern the existence of ornament Kumudawati at singup Pendhapa Ageng Mangkunegaran, Surakarta. This thesis attempts to identify, comprehend, and explain: Firtsly, life influence of Mangkunegaran palace before all to concepts think Mangkunegara VII; second, about concepts think Mangkunegara VII in initiative making of ornament kumudawati at singup Pendhapa Ageng Mangkungaran; and third about symbolic meaning consisting barbed in ornament kumudawati with Java culture order. Bearing in mind that culture is an element which influences the existence of ornament kumudawati, an overall understanding of the form, role, and meaning of ornament kumudawati is based on a cultural approach, that is a way of looking at culture as a system. Within this framework, culture is construed as aconcept which is used for analysis and at the same time as a model for study. The problems posed in the research for this thesis placed more emphasis on discovering the process and meaning, and for this reason, the paradigm of approach and strategy of reseach used was qualitative descriptive research. A phenomenological perspective with ethnographical dimensions was used. As such, this research is of an emic nature, as it is based on a means of emphatic understanding or verstehen within the framework of indigenous knowledge which is expressed in the from of â€œthick descriptionâ€.Keywords: simbolism, ornament kumudawati, Mangkunegaran